Determinants of Earnings Management on the Energy Sector - Zabidi, Naufal Rifqi; Wahyuni, Nanik; Mounadil, Abdelaziz (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Purpose: This study aims to examine the influence of company growth, profitability, and audit quality on earnings management, moderated by managerial ownership. The energy sector is chosen due to its strategic role in the economy and unique challenges, including high market volatility and significant capital requirements. Method: This research employs a quantitative approach using secondary data obtained from annual reports of energy companies listed on the Indonesia Stock Exchange (IDX) during 2020–2023. A purposive sampling technique resulted in a sample of 45 companies, comprising 180 data observations. Data analysis was conducted using panel data regression. Results: The findings reveal that company growth does not significantly influence earnings management. Profitability positively and significantly impacts earnings management, while audit quality has no significant effect. Furthermore, managerial ownership does not significantly moderate the relationships between company growth, profitability, and audit quality with earnings management. Implications: These results highlight the need for policymakers and stakeholders in the energy sector to focus on enhancing transparency and financial reporting. The insights provide valuable references for investors and researchers aiming to understand earnings management practices in industries with high market dynamics. Novelty: This study adds to the literature by incorporating managerial ownership as a moderating variable and focusing on the energy sector, which has been underexplored in previous research.